Hubungan Pengetahuan dan Sikap Perawat Dalam Menangani Orang Dengan HIV/AIDS di Rumah Sakit Ernaldi Bahar: Hubungan Pengetahuan dan Sikap Perawat Dalam Menangani Orang Dengan HIV/AIDS di Rumah Sakit Ernaldi Bahar - Penti Meka Pratiwi, Lisda Maria (STIKES Hesti Wira Sriwijaya, 2023)
AbstractBackground: The attitude of nurses in caring for HIV/AIDS patients will determine the patient's confidence and the success of treatment. The attitude of nurses can be influenced by the knowledge they have. The HIV/AIDS prevention training program has been carried out by but has not been evaluated in terms of knowledge and its effect on nurses' attitudes at the Ernaldi Bahar Hospital, South Sumatra Province. Ernaldi Bahar, South Sumatra Province. Objective: to determine the relationship between the level of knowledge of nurses and the attitude of nurses in dealing with HIV/AIDS patients at Ernaldi Bahar Hospital, South Sumatra Province. Method: This type of research is quantitative observational analytic with a cross-sectional approach. The population in this study were all nurses who worked in inpatient and outpatient methadone Ernaldi Bahar Hospital totaling 158 people with a sample of 40 people. Data analysis used the product moment correlation test followed by simple linear regression. Results: The average knowledge was 63.0 (9.67), the average attitude of the respondents was 60.95 (9.89). There is a relationship between knowledge and attitudes of nurses on HIV/AIDS patients at Ernaldi Bahar Hospital, South Sumatra Province. knowledge has an effect of 23.1% on the attitude variable. linear regression model. In this model, the regression equation model Y= 29,951+ 0,492 knowledge. Conclusion: The higher the knowledge, the more linear the attitude of nurses in treating HIV/AIDS patients at Ernaldi Bahar Hospital, South Sumatra Province. Suggestion: Form a nursing training team to increase nurses' knowledge about HIV/AIDS so that nurses' knowledge and attitudes can increase in caring for HIV/AIDS patients.Keywords: Knowledge, attitude, HIV/AIDS patientReading list : 38 (2012 – 2022)